The Framing Effect and Time Pressure on The Investment Decision: A Test for Prospect Theory and Fuzzy-Trace Theory - Amril; Narsa, I Made (Calitatea, 2022)
This study aimed to investigate the framing effect in investment decision making when the time pressure is present and to examine the capability of both prospect and fuzzy-trace theory in analyzing the framing effect. This study employed A 2x2x3 between-subjects experimental design. As many as 433 students participated in this experiment. The results of the study proved that both fuzzy-trace and prospect theory were capable of analyzing the framing effect on the investment decision. However, further test confirmed the superiority of fuzzy-trace in analyzing the framing effect compared to the prospect theory. It was also observed from framing and time pressure interaction that the presence of time pressure at prospect theory lowered the framing effect. An opposite result was confirmed from the fuzzy trace theory in which time pressure did not reduce the framing effect. Decision-makers preferred to perform simplification, summarizing the representation of information or to process the information qualitatively when simplification is possible.